Pengembangan Video Permainan Prisoner’s Dilemma 2D Platformer Dengan Menggunakan Unreal Engine - Bambang Irawan; Ramadhan, Azki (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
The dominance of 3D games has contributed to the fast growth of the video game industry in recent decades. Since 3D games have become so popular, 2D games might offer an intriguing alternative. Using the "Prisoner's Dilemma" game theory, this research attempts to construct a 2D game that will provide players with an engaging gaming experience. This work was developed using agile methodologies because of its flexibility, which enables rapid responses to evolving software development requirements. Black Box Testing and surveys revealed that the Prisoner's Dilemma is a fun, participatory game with branching narratives and conflict. Furthermore, player feedback was integrated through a survey with 28 respondents. The findings indicate that this video game has an appealing user interface (UI), a manageable difficulty level, is easily playable on a computer, has simple controls, and can entice players to attempt additional 2D video games.